2008
DOI: 10.1093/gerona/63.5.467
|View full text |Cite
|
Sign up to set email alerts
|

A Percentage Analysis of the Telomere Length in Parkinson's Disease Patients

Abstract: Telomeres are the repeated sequences at the chromosome ends which undergo shortening with cell division. The telomere shortening of the peripheral leukocytes is also facilitated by enhanced oxidative stress in various kinds of disease including ischemic heart disease, diabetes mellitus, apoplexy, and Alzheimer's disease. Telomere shortening in Parkinson's disease (PD) has not yet been reported. The pathogenesis for PD is also regarded to be associated with oxidative stress. We investigated 28 Japanese male PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 31 publications
7
47
0
Order By: Relevance
“…In a case-control study (96 cases and 172 age-matched controls), telomeres were not associated with the risk of PD (14). In a recent study by Guan et al (15), although the authors did not observe a statistical difference in mean telomere length of peripheral leukocytes between PD patients and control participants, a percentage analysis of telomere length suggested that telomere shortening was accelerated in PD patients in comparison to controls (15).…”
Section: Introductionmentioning
confidence: 89%
“…In a case-control study (96 cases and 172 age-matched controls), telomeres were not associated with the risk of PD (14). In a recent study by Guan et al (15), although the authors did not observe a statistical difference in mean telomere length of peripheral leukocytes between PD patients and control participants, a percentage analysis of telomere length suggested that telomere shortening was accelerated in PD patients in comparison to controls (15).…”
Section: Introductionmentioning
confidence: 89%
“…4,5 Telomere length has been observed to decrease with increases in cardiovascular risk factors such as hypertension, hyperlipidemia, diabetes, obesity and cigarette smoking. 6 We recently showed that the shortening of the telomeres in peripheral leukocytes was accelerated with advancing age 7 and it was also observed in patients with sarcoidosis 8 and Parkinson's disease 9 in the Japanese population.…”
mentioning
confidence: 96%
“…In a study of 28 Japanese male PD patients, leucocyte telomere length in PD patients was not significant different from those in controls. But mean telomere length in PD patients was found to be 5 kb shorter suggesting telomere shortening was accelerated in PD patients [23]. Additionally, Maede et al [24] investigated the age-associated alterations of subtelomeric methylation in Japanese PD patients.…”
Section: The Role Of Telomere and Telomerase In Degenerative Diseasesmentioning
confidence: 99%